Factors associated with suicide risk among Chinese adults: A prospective cohort study of 0.5 million individuals. - Rongqin Yu; Yiping Chen; Liming Li; Junshi Chen; Yu Guo; Zheng Bian; Jun Lv; Canqing Yu; Xianmin Xie; Dan Huang; Zhengming Chen; Seena Fazel (PLoS Medicine)
Background Suicide is a leading cause of death in China and accounts for about one-sixth of all suicides worldwide. The objective of this study was to examine the recent distribution of suicide and risk factors for death by suicide. Identifying underlying risk factors could benefit development of evidence-based prevention and intervention programs. Methods and findings We conducted a prospective study, the China Kadoorie Biobank, of 512,715 individuals (41% men, mean age 52 years) from 10 (5 urban, 5 rural) areas which are diverse across China in geographic locations, social economic developmental stages, and prevalence of disease patterns. After the baseline measurements of risk factors during 2004 to 2008, participants were followed up for suicide outcomes including suicide and possible suicide deaths. Risk factors, such as sociodemographic factors and physical and mental health status, were assessed by semistructured interviews and self-report questionnaires. Suicide and possible suicide deaths were identified through linkage to the local death registries using ICD-10 codes. We conducted Cox regression to calculate hazard ratios (HRs) for suicide and for possible suicide in sensitivity analyses. During an average follow-up period of 9.9 years, 520 (101 per 100,000) people died from suicide (51.3% male), and 79.8% of them lived in rural areas. Sociodemographic factors associated with increased suicide risk were male gender (adjusted hazard ratios [aHR] = 1.6 [95% CI 1.4 to 2.0], p < 0.001), older age (1.3 [1.2 to 1.5] by each 10-yr increase, p < 0.001), rural residence (2.6 [2.1 to 3.3], p < 0.001), and single status (1.7 [1.4 to 2.2], p < 0.001). Increased hazards were found for family-related stressful life events (aHR = 1.8 [1.2 to 1.9], p < 0.001) and for major physical illnesses (1.5 [1.3 to 1.9], p < 0.001). There were strong associations of suicide with a history of lifetime mental disorders (aHR = 9.6 [5.9 to 15.6], p < 0.001) and lifetime schizophrenia-spectrum disorders (11.0 [7.1 to 17.0], p < 0.001). Links between suicide risk and depressive disorders (aHR = 2.6 [1.4 to 4.8], p = 0.002) and generalized anxiety disorders (2.6 [1.0 to 7.1], p = 0.056) in the last 12 months, and sleep disorders (1.4 [1.2 to 1.7], p < 0.001) in the past month were also found. All HRs were adjusted for sociodemographic factors including gender, age, residence, single status, education, and income. The associations with possible suicide deaths were mostly similar to those with suicide deaths, although there was no clear link between possible suicide deaths and psychiatric factors such as depression and generalized anxiety disorders. A limitation of the study is that there is likely underreporting of mental disorders due to the use of self-report information for some diagnostic categories. Conclusions In this study, we observed that a range of sociodemographic, lifestyle, stressful life events, physical, and mental health factors were associated with suicide in China. High-risk groups identified were elderly men in rural settings and individuals with mental disorders. These findings could form the basis of targeted approaches to reduce suicide mortality in China.